Bureaucracy-democracy compatibility - An analysis - Sharma, Subhash (2000)
With a brief look on the conceptual interpretations of the term `bureaucracy' by Max Weber and experts of different disciplines, the author attempts a systematic analysis of compatibility of bureaucracy with democracy through testing four critical hypotheses of: (1) dependence (bureaucracy draws its power and authority from democracy), (2) securing unity and integrity of nation (bureaucracy's crucial instrumentality therein), (3) impartiality in securing all interests, perticularly that of the poor (to realise democratic principles), and (4) rendering of specialised and professional service (in both policy formulation and implementation). Before arriving at his conclusion that a right-sized bureaucracy can be more efficient and effective through democratic mechanisms, he picks up for discussion various issues affecting bureaucracy-democracy relationship pertaining to exercising of administrative discretion, commitment versus neutrality, and centralisation versus decentralisation. - Reproduced
Keywords: Democracy; Bureaucracy